PHYSICO-CHEMICAL BASIS OF OBTAINING DOUBLE SUPERPHOSPHATE FROM KARATOG PHOSPHORITE - Sirojiddin Zoirov Saxomiddin ugli (Web of Journals Publishing, 2024)
This article explores the physical-chemical processes involved in the production of Brown Superphosphate from Karatog phosphorite, an essential step in fertilizer manufacturing. The study delves into the acidulation and solubilization methods, presenting results and a comprehensive discussion on the efficacy of the process.
Keywords: Brown superphosphate, karatog phosphorite, phosphate rock, fertilizer, acidulation, solubilization.